Pengaruh Arah Pengerolan dan Orientasi Butir Logam Terhadap Sifat Mekanik Magnesium AZ31B Untuk Aplikasi Implan Biomedik Mampu Terdegradasi (Biodegradable Implant) - Maherariyat Maherariyat; Mohammad Baddarudin; Irza Sukmana; Sugiyanto Sugiyanto; Asep Sukohar; A Yudi Eka Risano (Universitas Muhammadiyah Metro, 2025)
This study investigates the effects of rolling direction and grain orientation on the mechanical properties of AZ31B magnesium alloy, with a focus on its application in biodegradable implants. The research was conducted experimentally by preparing tensile test specimens from AZ31B sheet plates, cut in two different directions: parallel (0Â°, X) and perpendicular (90Â°, Y) to the rolling direction. Static tensile testing was performed in accordance with ASTM B557 standards to measure the material's mechanical properties. The results indicate mechanical anisotropy, where specimens in the X direction exhibited an average yield strength of 198.78 MPa, while specimens in the Y direction achieved a value of 78.21 MPa, only 39.3% of the X direction value. This difference is attributed to the formation of crystallographic texture during the rolling process. The modulus of elasticity showed similar properties, with values of 44-45 GPa in both directions. These findings demonstrate that grain orientation and rolling direction significantly affect the mechanical properties of the material, which is crucial in designing degradable magnesium AZ31B implant materials.